Antioxidant potential of lichen species and their secondary metabolites. A systematic review. (2nd January 2016) - Fernández-Moriano, Carlos; Gómez-Serranillos, María Pilar; Crespo, Ana
Abstract: Context : Pharmacological interest of lichens lies in their capacity to produce bioactive secondary metabolites, being most of them phenolic compounds with reactive hydroxyl groups that confer antioxidant potential through various mechanisms. Increasing incidence and impact of oxidative stress-related diseases (i.e., neurodegenerative disorders) has encouraged the search of new pharmacological strategies to face them. Lichens appear to be a promising source of phenolic compounds in the discovery of natural products exerting antioxidant activity. Objective : The present review thoroughly discusses the available knowledge on antioxidant properties of lichens, including both in vitro and in vivo studies and the parameters assessed so far on lichen constituents. Methods : Literature survey was performed by using as main databases PubMed, Google Scholar, Scopus, Science Direct, and Recent Literature on Lichens. We reviewed 98 highlighted research articles without date restriction. Results : Current report collects data related to antioxidant activities of more than 75 lichen species (from 18 botanical families) and 65 isolated metabolites. Much information comes from in vitro investigations, such as chemical assays evaluating radical scavenging properties, lipid peroxidation inhibition, and reducing power of lichen species and compounds; similarly, research on cellular substrates and animal models generally measures antioxidant enzymes levels and other antioxidant markers, such as glutathione levels or tissue peroxidation. Conclusion : Since consistent evidence demonstrated the contribution of oxidative stress on the development and progression of several human diseases, reviewed data suggest that some lichen compounds are worthy of further investigation and better understanding of their antioxidant and neuroprotective potentials.